The Learning of Conceptual Categories for Students with Level 1 Autism Spectrum Disorder - Rúa, Manuel Ojea (Journal of Intellectual Disability - Diagnosis and Treatment, 2016)
This article presents a study where the overall objective is to measure any changes found as a result of the application of a program to facilitate the development of the semantic memory of people with Level 1 Autism Spectrum Disorder, following the implementation of a specific program to facilitate the creation of conceptual categories. The study, based on a quasi-experimental design, analyzes the effectiveness of the program designed around four cognitive variables, comparatively observed in three groups of participants (N:19), distributed across one experimental group (N:7) and two control groups (made up of 7 and 5 participants respectively), conducted over three successive measures, 1 pre-test and 2 post-test measures at 6-month intervals. The results, found by repeatedly testing measures of intra-subject effects, show the effectiveness of the designed program, as it has aided in the development of meaningful learning for the members of the experimental group.